Serum E-selectin concentration is associated with risk of metabolic syndrome in females. - Chien-Hsing Lee (PLoS ONE, 2019)
OBJECTIVES:Traits of metabolic syndrome (MetS) and biomarkers of inflammation and endothelial dysfunction were examined. We investigated the differences of various biomarkers among individuals with or without Mets in a gender-specific manner. The gender-specific associations between E-selectin and MetS were further evaluated. METHODS:A total of 205 patients were recruited from the outpatient clinics of Tri-Service General Hospital, Taipei, Taiwan. Inclusion criteria were age between 20-75 years and BMI < 35 kg/m2. Demographic, anthropometric and MetS index data were compared between genders. Markers of inflammation and endothelial dysfunction were compared between individuals with or without MetS by gender. RESULTS:Age-adjusted E-selectin values showed significant positive correlations with BMI, waist-hip ratio, fasting plasma glucose, systolic and diastolic blood pressure, triglycerides, TNF-α, hsCRP and ICAM-1, and inverse correlation with HDL cholesterol. E-selectin levels were positively correlated with numbers of MetS components in females (P < 0.001) but not in males (P = 0.125). CONCLUSIONS:Increased E-selectin levels are significantly associated with increased MetS risk in females, but not in males.